تقييم تأثير نمط توزع نقاط الضبط على تصحيح التشوهات الهندسية في المرئيات الفضائية - الخليل, عمر; علي, أحمد; الدبل, خلود (Latakia University Journal -Engineering Sciences Series, 2018)
There are many sources that cause the emergence of geometric deformations in satellite images. These deformations are accumulated and not present singly in the image. Therefore, it is necessary to correct the image by applying a process called "geometric correction". Two methods are available to coorect the images. These ones are the parametric and the non-parametric methods. Non-parametric approach does not require knowledge of the parameters of the used sensor. Control points and geometric transformations are considered as the two main components in the non-parametric approach. Usually, barrel and perspective deformations are present in satellite images. In this paper, we will study the impact of the distribution of control points and the degree of geometric transformation on the correction of the image of these deformations. This paper presents simulation test to investigate the effect of three different distribution patterns of control points on three different distortions and three types of geometric transformation using grid images. It has been demonstrated that the control points located in different parts of the image have different deformation rates, the control points distributed in the center of the image suffers less deformations. تنشأ التشوهات الهندسية في المرئيات الفضائية من عدة مصادر وهي تؤثر على كامل المرئية بشكل مشترك. وهذه التشوهات تؤثر على النوعية الهندسية للبيانات المكانية المقتطعة من المرئية ولذلك لابد من تصحيحها قبل ذلك بعملية تسمى التصحيح الهندسي. يتوفر أسلوبان لتصحيح المرئيات هندسياً وهما الأسلوب غير المباشر Parametric approach والأسلوب المباشر Non-parametric approach وهو لا يتطلب معرفة معاملات المستشعر المستخدم. تعتبر نقاط الضبط Control points والتحويلات الهندسية مكونين أساسيين في الأسلوب المباشر للتصحيح. عادة ما تتواجد تشوهات التكور Barrel والمنظورية Perspective (شاقولية وأفقية) في المرئيات الفضائية. في هذا البحث سنقوم بدراسة تأثير نمط توزيع نقاط الضبط ودرجة التحويل الهندسي على تصحيح المرئية من هذه التشوهات. تم إجراء الاختبار بطريقة المحاكاة للتحقق من تأثير ثلاثة أنماط توزيع مختلفة من نقاط الضبط على تصحيح ثلاثة تشوهات مختلفة باستخدام ثلاثة أنواع من التحويلات الهندسية (كثيرات الحدود) مطبقة على مرئيات لها شكل شبكة. . لقد تمت البرهنة على أن نقاط الضبط المتواجدة في مناطق مختلفة من الصورة تملك نسب تشوه مختلفة وأن نقاط الضبط الموزعة في مركز المرئية تعاني تشوهاً أقل.